STRUCTURAL AND OPTICAL PROPERTIES OF GaAs1-xBix/AlyGa1-yAs QUANTUM WELL HETEROSTRUCTURES GROWN BY MOLECULAR BEAM EPITAXY - Almunyif, Amjad (2024)
This work reports on the effect of Bi concentration on the structural and optical properties of dilute GaAs(1− x)Bix Single Quantum Well (SQWs) grown by molecular beam epitaxy (MBE) on (001) GaAs substrates. The influence of Bi content has been studied by X-Ray Diffraction (XRD), Raman spectroscopy, and Photoluminescence (PL) measurements. The PL spectra exhibit a redshift in energy as the Bi concentration increases from 2.7% to 5.1%. This result is in good agreement with Raman measurements, which showed that Bi induces tensile stress as evidenced by the redshift of the emission of LO phonons and the increase of the concentration of holes with increasing Bi concentration. Furthermore, the XRD data revealed that the SQWs exhibit structural changes as evidenced by the displacement of the GaAs(1-x)Bix peak as a function of Bi concentration, which is consistent with the PL results. The integrated PL intensity as a function of inverse temperature confirmed two types of defects, namely lattice disorder and Bi clusters. This study also explored the structural and optical properties of GaAs(1-x)Bix /GaAs heterostructures with varying numbers (1 to 5) of QWs grown on (001) GaAs substrates by MBE. By employing PL spectroscopy, the impact of the number of QWs on their optical properties was assessed. A broadening was observed in the PL spectra as the number of QW layers increased, and this was attributed to structural disorder and non-uniform Bi incorporation. These findings are supported by XRD results which showed structural changes in (004) GaAs(1-x)Bix peak as the number of QWs layers increased. Further investigations into the PL spectra indicated Bi content non-homogeneities within the QW layers and a notable segregation of Bi into layers beyond the first QW as evidenced by the increased value of Bi% in subsequent QWs. These results are consistent with Raman measurements, which demonstrated that as the number of QWs increases the LO phonon peak blueshifts and becomes broader, evidencing structural disorder induced by the presence of Bi in every QW layer. A departure from the expected S-shape behaviour of the temperature-dependent PL peak energy characteristics suggests a low density of localized defects in these structures. The analysis of the integrated PL intensity as a function of temperature revealed two distinct thermal quenching processes, suggesting an increase in Bi-related defects with a higher number of QWs. However, this defect density seems to decrease within the first QW as the number of QW layers increases, pointing towards a complex interplay between quantum confinement and defect dynamics. These findings confirm that the optimal number of GaAs(1-x)Bix/GaAs QW layers is strongly influenced by growth conditions and material properties, highlighting the intricate nature of these semiconductor structures and the critical role of precise growth conditions in achieving desired optical properties. The impact of varying Bi concentrations on the optical properties of GaAs(1− x)Bix/GaAs/ Al0.3Ga0.7As Separate Confinement Heterostructures (SCHs) was also investigated using the PL technique. The investigation revealed that band-to-band recombination of uncorrelated carriers is the predominant emission mechanism with PL signals originating from GaAs(1-x)Bix QWs rather than defects or impurities. It was found that increasing Bi content induces a redshift in PL spectra as expected but with notable enhancement in PL intensity when Bi increased from 2.7% to 4%. This PL improvement might be due to Bi-induced localisation effects and/or a reduction in the density of defects due to higher Bi incorporation. However, by increasing the Bi concentration from 4% to 5.1%, the PL intensity decreased, meaning an increase in the nonradiative recombination centres due to defects and alloy disorder, which become more significant with higher Bi incorporation. The study further examined the influence of Al0.3Ga0.7As barriers on these SCHs structures by comparing them with SQWs with only GaAs barriers. The role of the additional Al0.3Ga0.7As barrier was to enhance carrier confinement and therefore optical quality. For 2.7% Bi content, a significant increase in PL intensity was observed for SCHs as compared with SQWs. However, the PL efficiency of SCHs samples with higher Bi concentrations (4% and 5.1%) degraded as compared with similar GaAs(1-x)Bix/GaAs SQWs. These findings suggest that to maximise the performance of GaAs(1-x)Bix QWs for optoelectronic applications, a careful optimization of Bi content and growth conditions is crucial. These studies, which highlight the complex interplay between Bi concentration, structure design, and optical properties, offer valuable insights into the design and optimization of GaAs(1-x)Bix-based devices for advanced optoelectronic devices.